Learning Using Patterns and Memory in a Systems Engineering Program (2019)
This article is a product of the research Project “A model with BBL in the improvement of the learning process using affective techniques” approved by Vicerrectoria de Investigaciones from Universidad Tecnológica de Pereira. This project takes place in the Universidad Tecnológica de Pereira, Facultad de Ingenierías, Programa de Ingeniería de Sistemas y Computación”. It contains the description of the experience in the 1st Programming course to exploit the brain characteristics around patterns and memory in the simplification of the learning process in the context of the matter. You can find some concepts and the invitation to adopt this methodology in the technological field.